Factors influencing collaborative information behavior in a digital environment: a study in Malaysian public sector / Siti Rohani Abdul Hamid and Fadhilah Aman - Abdul Hamid, Siti Rohani; Aman, Fadhilah (Faculty of Information Management, 2022)
The increasing number of information resources and systems has resulted in too much information gathered for a specific task. To assist in getting the information sources needed, collaborated information sharing among individuals and departments is necessary to ensure the right decisions making in an organization. This study aims to address the lack of studies investigating the factors responsible for enhancing collaborative information behaviour (CIB), particularly in a digital environment in the public sector. The data was acquired via an online questionnaire as part of the survey research procedure. The survey was sent to 150 accountants in Accounting General’s Department (AGD), Malaysia, through purposive sampling, which provided evidence of the significant positive influence of social influence and digital literacy in enhancing the level of CIB in the organization.